Improved simulation of Indian summer monsoon in latest NCEP climate forecast system free run. (25th July 2013) - Saha, Subodh K.; Pokhrel, Samir; Chaudhari, Hemantkumar S.; Dhakate, Ashish; Shewale, Swati; Sabeerali, C. T.; Salunke, Kiran; Hazra, Anupam; Mahapatra, Somnath; Rao, A. Suryachandra
ABSTRACT Simulation of Indian summer monsoon features by latest coupled model of National Centers for Environmental Prediction (NCEPs) Climate Forecast System version 2 (CFSv2) is attempted in its long run. Improvements in the simulation of Indian summer monsoon as compared with previous version (CFSv1) is accessed and areas which still require considerable refinements are introduced. It is found that, spatial pattern of seasonal mean rainfall and wind circulations are more realistic in CFSv2 as compared with CFSv1. Variance and northward propagation of intraseasonal oscillation (ISO), which also contribute to the seasonal mean rainfall are remarkably improved. However, the central Indian dry bias still persists and amplified. Pervasive cold bias in surface (2 m air temperature) as well as in the whole troposphere is further increased in CFSv2. These cold biases may be partly attributed to the lack of model's ability to realistically simulate the ratio of convective and stratiform rainfall. Sea‐surface temperature (SST) over the Indian Ocean is underestimated in CFSv2. However, CFSv1 shows east–west dipole structure in the bias. The teleconnection of El Nino Southern Oscillation (ENSO) and Indian summer monsoon rainfall (ISMR) in terms of Niño3 SST and monsoon rainfall correlation is more realistic in the latest version of the model. Overall, there are substantial improvements in CFSv2 as compared with CFSv1, but it has to evolve further to realistically simulate the mean and variability of ISMR.